Calculator search results

Formula
Solve the equation
Answer
circle-check-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
expand-arrow-icon
Calculate the differentiation
Answer
circle-check-icon
expand-arrow-icon
Graph
$y = 3 x + 2$
$x$-intercept
$\left ( - \dfrac { 2 } { 3 } , 0 \right )$
$y$-intercept
$\left ( 0 , 2 \right )$
$y = 3x+2$
$x = \dfrac { 1 } { 3 } y - \dfrac { 2 } { 3 }$
$ $ Solve a solution to $ x$
$y = \color{#FF6800}{ 3 } \color{#FF6800}{ x } + 2$
$ $ Move $ x $ term to the left side and change the sign $ $
$y \color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = 2$
$\color{#FF6800}{ y } - 3 x = 2$
$ $ Move the rest of the expression except $ x $ term to the right side and replace the sign $ $
$- 3 x = 2 \color{#FF6800}{ - } \color{#FF6800}{ y }$
$- 3 x = \color{#FF6800}{ 2 } \color{#FF6800}{ - } \color{#FF6800}{ y }$
$ $ Organize the expression $ $
$- 3 x = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$\color{#FF6800}{ - } \color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ - } \color{#FF6800}{ y } \color{#FF6800}{ + } \color{#FF6800}{ 2 }$
$ $ Change the sign of both sides of the equation $ $
$3 x = y - 2$
$\color{#FF6800}{ 3 } \color{#FF6800}{ x } = \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 2 }$
$ $ Divide both sides by the same number $ $
$\color{#FF6800}{ x } = \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$x = \left ( y - 2 \right ) \color{#FF6800}{ \div } \color{#FF6800}{ 3 }$
$ $ Convert division to multiplication $ $
$x = \left ( y - 2 \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \left ( \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \right ) \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$ $ Multiply each term in parentheses by $ \dfrac { 1 } { 3 }$
$x = \color{#FF6800}{ \dfrac { 1 } { 3 } } \color{#FF6800}{ y } \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$x = \dfrac { 1 } { 3 } y \color{#FF6800}{ - } \color{#FF6800}{ 2 } \color{#FF6800}{ \times } \color{#FF6800}{ \dfrac { 1 } { 3 } }$
$ $ Calculate the product of rational numbers $ $
$x = \dfrac { 1 } { 3 } y \color{#FF6800}{ - } \color{#FF6800}{ \dfrac { 2 } { 3 } }$
$\dfrac {d } {d x } {\left( y \right)} = 3$
Calculate the differentiation of the logarithmic function
$\dfrac {d } {d \color{#FF6800}{ x } } {\left( \color{#FF6800}{ 3 } \color{#FF6800}{ x } \color{#FF6800}{ + } \color{#FF6800}{ 2 } \right)}$
$ $ Calculate the differentiation $ $
$\color{#FF6800}{ 3 }$
$ $ 그래프 보기 $ $
Linear function
Solution search results
search-thumbnail-$7.$ $\dfrac {x+2} {7}+\dfrac {y-x} {4}=2x-8$ 
$\dfrac {2y-3x} {3}+2y=3x+4$
7th-9th grade
Calculus
search-thumbnail-$7$ $\dfrac {x+2+} {7}\dfrac {y-x} {4}=2x-8$ 
$\dfrac {2y-3x} {3}$ $+2y=3x+4$
7th-9th grade
Algebra
Have you found the solution you wanted?
Try again
Try more features at QANDA!
Search by problem image
Ask 1:1 question to TOP class teachers
AI recommend problems and video lecture
apple logogoogle play logo